Akhlak menurut Al-Ghazali dan Buya Hamka: Suatu Perbandingan dengan Pendekatan Filosofis - Erisa Widiana Sukirman (UIN Sunan Gunung Djati Bandung, 2023)
The main goal of Islam is to shape human morals for the better. Through this goal, Islam instills through aspects of morals that can be learned by Muslims in particular and in general by humans. This study aims to determine the concept of morality according to Al-Ghazali and Buya Hamka and to find out the similarities and differences. This research uses a qualitative approach with a library research technique with a qualitative approach. The results of this study found differences of opinion regarding morality. Moral according to Al-Ghazali is a trait that has been embedded in the soul and is easily realized in action without having to think about it first. Meanwhile, according to Buya Hamka, morality is the goal of humans to improve themselves, therefore human morality is recognized from its character.